Application of Cluster Analysis for Identifying Homogenous Zones of Operation of Agricultural Enterprises - KobylynskaТ. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The cluster analysis ofagricultural enterprises is made by region Ukraine. The analysis is made by the agricultural sector and its subsectors: plant-growing and animal husbandry. Homogenous regional zones characterizing the performance agricultural enterprises are identified. The clustering is made using SPPS software. In the problems involved in the cluster analysis Euclidean distance is used. The cluster analysis is used for constructing green maps illustrating the impact agricultural activities at enterprises on the production output of the agricultural sector and its subsectors: plant-growing and animal husbandry. The constructed dendrogram was used fo r creating two clusters showing low and high performance of the plant-growing sector. The first cluster includes 17 regions Ukraine have high performance along with low application mineral fertilizers: Vinnytsya region, Dnipropetrovsk region, Donetsk region, Zhytomyr region, Zaporizhzhya region, Kyiv region, Kirovohrad region, Luhansk region, Mykolaiv region, Odesa region, Poltava region, Sumy region, Kharkiv region, Kherson region, Khmelnytsk region, Cherkasy region, andChernihiv region. The second cluster includes 7 regions with low plant-growing performance along with intensive application mineral fertilizers: Volyn region, Transkarpaty region, Ivano- Frankivsk region, Lviv region, Rivne region, Ternopil region, Chernivtsi region. The characteristics of regional zones by agricultural production output, numbers cattle and poultry, and agriculture performance give evidence that in view ofthe similarity in the conditions their territories, they require similar measures aiming to improve business environment in the sector and mechanisms fo r the development agroindustrial complex in Ukraine.